2015
DOI: 10.1007/s00436-015-4409-z
|View full text |Cite
|
Sign up to set email alerts
|

Angelica sinensis (Umbelliferae) with proven repellent properties against Aedes aegypti, the primary dengue fever vector in Thailand

Abstract: Botanical resources with great diversity in medicinal and aromatic plants are a rich and reliable source for finding insect repellents of plant origin, which are widely popular among today's consumers. Although some herbal-based repellents have been proven comparable to or even better than synthetics, commercially available natural repellents generally tend to be expensive, with short-lived effectiveness. This critical flaw leads to ongoing research for new and effective repellents, which provide longer protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…The percentage composition of the remaining 18 compounds ranged from 0.16 to 3.70 %. This GC-MS profile corresponded relatively to that of AHE analyzed in a previous study [ 21 ], which revealed the presence of 13 chemicals, representing 95.17 % of the total quantities. The most abundant compound was 3- N -butylphthalide (70.14 %), whereas ligustilide (8.34 %) and butylidenephthalide (4.85 %) were minor constituents.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The percentage composition of the remaining 18 compounds ranged from 0.16 to 3.70 %. This GC-MS profile corresponded relatively to that of AHE analyzed in a previous study [ 21 ], which revealed the presence of 13 chemicals, representing 95.17 % of the total quantities. The most abundant compound was 3- N -butylphthalide (70.14 %), whereas ligustilide (8.34 %) and butylidenephthalide (4.85 %) were minor constituents.…”
Section: Resultssupporting
confidence: 75%
“…1 ) is a promising plant that has attracted substantial interest. Preliminary repellent assessments of various plant products, essential oils and solvent extracts, against laboratory-reared female Aedes aegypti mosquitoes highlighted A. sinensis hexane extract (AHE) as offering the longest-lasting protection time of 7.5 (6.5–8.5) h [ 21 ]. Phthalides, including 3- N -butylphthalide (70.14 %), ligustilide (8.34 %) and butylidenephthalide (4.85 %) were reported as the main and minor constituents in AHE, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the EO of A. dahurica showed a significant toxic effect against early fourth-stage larvae of Aedes aegypti, with a LC 50 value of 43.12 ppm. In another study, out of 33 plant species tested, A. sinensis EO showed the best repellent activity against Aedes aegypti, with a median complete protection time of 7.0 h [ 35 ].…”
Section: Biological Activities Of Angelica Essementioning
confidence: 99%
“…Diels, is a perennial herb belonging to family Apiaceae, and commonly used in Traditional Chinese Medicine since ancient times (Zhang and Cheng, 1989). In addition, A. sinensis is widely used as an ingredient in cosmetic and health beverage at present (Chen, 2002;Champakaew et al, 2015). In order to meet its demand, areas of continuous cropped for A. sinensis have been increased dramatically in the last decade.…”
Section: Introductionmentioning
confidence: 99%